Deglacial heat uptake by the Southern ocean and rapid northward redistribution via antarctic intermediate water - Poggemann, David Willem; Bahr, André (Paleoceanography and paleoclimatology, 2018)
Deglacial Mg/Ca‐based intermediate water temperature changes in the tropical W‐Atlantic - Prominent AAIW heat was supplied to the tropical Atlantic during AMOC perturbations after a detour via the So...